AGAS SCIARID (DIPTERA: SCIARIDAE): SUATU KAJIAN PUSTAKA - Susrama, I Gede Ketut (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
In Bali, the sciarid gnat is called “Lulut”, a small flying flies which belong to some families, many genus and a lot of species which having a spiritual value. At the time a group of gnat larva move out from the underground to soil surface, a certain ritual will be surely performed by the land owner at the location where gnat larva occured. Many people wondering, what kind of animal lulut is?. This review article tries to answer. Various matters from entomological aspect to agricultural aspect such as morphology, life cycle, habitat, aggregation, migration, its role as a crop pest and also about how to control them are discused.